Securing Database Management Systems using RAM Serial Numbers - Azeez, Sapan Noori; Varol, Serkan (Ieee, 2019)
For any Management System (DBMS) program, protection of the program is the most important element of recognizing faults in system quality that can sometimes lead to system failure. When launching any new product, we aim to use RAM serial number method makes its use simpler and easier for the developer and all users in the future. In addition, providing security techniques for databases (DBs) is very critical when defending against hackers to prevent them from making copies of the program and accessing the source code. Protecting a database so that nobody can access it without permission is necessary due to copyright principles. In this paper, the existing kinds of encryption methods have been obtained in ITC: SW and HW encryption by utilizing the serial number of random access memory (RAM), which is a part of the PC that has its own unique serial number.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Database Management System (DBMS); Software Encryption (SE); Random Access Memory (RAM); Database (DB); Information Technology Computer (ITC); Software (SW); Hardware(HW)